Jejunal intussusception due to intestinal metastasis of cutaneous malignant melanoma: clinical case report. - Invernizzi, Mariana; Ormachea, Ernesto; Valsangiacomo, Pablo (Cirugía del Uruguay, 2025)
Melanoma is a malignant neoplasm that predominantly affects the skin and accounts for 1–3% of all neoplasms. It is characterized by its high metastatic potential, frequently involving the gastrointestinal tract, with the jejunum and ileum being the most commonly affected sites. Most patients with gastrointestinal metastases are asymptomatic or present with nonspecific symptoms. Complications are uncommon; among them, intestinal obstruction is notable, with intussusception being a rare form of presentation. The aim of this report is to present the clinical case of a 63-year-old male patient with a previous diagnosis of cutaneous malignant melanoma who, two years later, presented with clinical and imaging findings consistent with intestinal obstruction. An emergency laparotomy was performed, revealing an intussusception at the jejunal level and a nodular mass in the mesentery. Segmental resection with anastomosis was carried out. Histopathological analysis confirmed cutaneous melanoma metastasis. The early detection of gastrointestinal metastases presents a true diagnostic challenge. Given the high frequency of metastatic involvement of the jejunum and ileum, a high index of suspicion is essential in the presence of nonspecific symptoms such as abdominal pain, systemic compromise, and/or anemia. In such cases, diagnostic studies with greater accuracy such as positron emission tomography combined with computed tomography (PET-CT) and capsule endoscopy should be considered. Surgical treatment of gastrointestinal metastases has been shown to improve prognosis and increase survival, compared to patients with unresected metastatic disease.